The in vitro and in vivo antibacterial activities of uniflorous honey from a medicinal plant, Scrophularia ningpoensis Hemsl., and characterization of its chemical profile with UPLC-MS/MS. (5th October 2022) - Lin, Tianxing; Huang, Lei; Cheng, Ningna; Wang, Yuzhen; Ning, Zhen; Huang, Shaokang; Wu, Yuanhua; Chen, Tianbao; Su, Songkun; Lin, Yan
Abstract: Ethnopharmacological relevance: According to the Compendium of Materia Medica, honey has been used as a traditional medicine in treatment against mucositis, tinea, hemorrhoids and psoriasis. In complementary medicine, due to its significant antimicrobial activity, honey has been widely used as a remedy for skin wounds and gastrohelcosis for thousands of years. Aim of the study: This study is aimed at exploring the antimicrobial activity and mechanisms of honey sourced from medicinal plants, and revealing the composition-activity relationship, to facilitate their complementary and alternative application in the therapy of bacterial infectious diseases. Materials and methods: Eight kinds of medicinal plant-derived uniflorous honey, native to China, were gathered. Their antimicrobial activities were evaluated in vitro, and then in vivo with the systemically infected mouse model and the acute skin infection model. SYTOX uptake assay, scanning electron microscopy, DNA binding assay, and quantitative real-time PCR, were carried out to elucidate the antibacterial mechanisms. This was followed by an investigation of the componential profile with the UPLC-MS/MS technique. Results: It was found that Scrophularia ningpoensis Hemsl. (figwort) honey ( S. ningpoensis honey) exhibited broad-spectrum and the strongest antibacterial potency (MICs of 7.81–125.00%, w/v), comparable to manuka honey. In the in vivo assays, S. ningpoensis honey significantly decreased the bacterial load of the muscles under the acute MRSA-infected skin wounds; the sera level of TNF-α in the S. aureus and P. aeruginosa -infected mice decreased by 45.38% and 51.75%, respectively, after the treatment of S. ningpoensis honey (125 mg/10 g). It was capable of killing bacteria through disrupting the cell membranes and the genomic DNA, as well as down-regulating the expression of genes associated with virulence, biofilm formation and invasion, including icaA, icaD, eno, sarA, agrA, sigB, fib and ebps in S. aureus, and lasI, lasR, rhlI, rhlR and algC in P. aeruginosa . Apart from H2 O2, some other nonperoxide compounds such as adenosine, chavicol, 4-methylcatechol, trehalose, palmitoleic acid and salidroside, might play a vital role in the antibacterial properties of S. ningpoensis honey. Conclusions: This is the first study to thoroughly investigate the antibacterial activity, mode of action, and componential profile of S. ningpoensis honey. It suggested that S. ningpoensis honey might be a potential supplement or substitute for manuka honey, for the prevention or treatment of bacterial infections. It will facilitate the precise application of medicinal plant-sourced honey, provide a new thread for the development of antibacterial drugs, and assist in the distinction of different kinds of honey. Graphical abstract: Image 1 Highlights: S. ningpoensis honey exhibited marked antibacterial activity. It induced bacterial death through disrupting cell membrane and genomic DNA. It down-regulated virulence, biofilm and invasion-related genes of bacteria. H2 O2 and nonperoxide compounds contributed to the antibacterial properties. First study revealing antibacterial activity and mechanisms of S. ningpoensis honey.